2020
DOI: 10.1155/2020/7857043
|View full text |Cite
|
Sign up to set email alerts
|

99-Case Study of Sporadic Aortic Dissection by Whole Exome Sequencing Indicated Novel Disease-Associated Genes and Variants in Chinese Population

Abstract: Background. In this study, the whole exome sequencing in human aortic dissection, a highly lethal cardiovascular disease, was investigated to explore the aortic dissection-associated genes and variants in Chinese population. Methods. Whole exome sequencing was performed in 99 cases of aortic dissection. All single nucleotide polymorphisms (SNPs), insertions/deletions (InDels), and copy number variations (CNVs) were filtered to exclude the benign variants. Enrichment analysis and disease-gene correlation analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…DOI: 10.1161/ATVBAHA.121.316237 pathways is partly overlapping with the syndromic and nonsyndromic familial TAAs. 36,37 In AAA, genetic studies have identified 87 genes or loci with polymorphisms on AAA patients but only 10 of them with strong or moderate evidence for association with the disease. These are related to cholesterol metabolism, atherosclerosis, inflammation, and hypertension.…”
Section: Genetics and Cell Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…DOI: 10.1161/ATVBAHA.121.316237 pathways is partly overlapping with the syndromic and nonsyndromic familial TAAs. 36,37 In AAA, genetic studies have identified 87 genes or loci with polymorphisms on AAA patients but only 10 of them with strong or moderate evidence for association with the disease. These are related to cholesterol metabolism, atherosclerosis, inflammation, and hypertension.…”
Section: Genetics and Cell Plasticitymentioning
confidence: 99%
“…Even a broader range of somatic mutations have been detected in a sporadic TAA; although, a list of risk genes and affected signaling pathways is partly overlapping with the syndromic and nonsyndromic familial TAAs. 36,37…”
Section: Genetics and Cell Plasticitymentioning
confidence: 99%
“…14,15 Previous research found that 2 SNPs in the FBN1 gene, rs2118181 and rs10519177, were found to be associated with thoracic aortic dissection (TAD), nonclamped thoracic aortic aneurysm (TAA), and TAAD in previous studies. 12,16 However, to our knowledge, no related research about the association between rs201170905 or rs11070646 of FBN1 gene and DeBakey type III AD has been reported. In this study, we observed that individuals with GG genotype of rs11070646 and rs201170905 were at an increased risk for DeBakey type III AD.…”
Section: Discussionmentioning
confidence: 95%
“…Concerning syndromic TAA in patients diagnosed as vEDS, few post-mortem cases were reported in 2010 [ 107 ], and 33 unrelated individuals or families were found to carry COL3A1 splicing mutations or small deletions partially removing splice-junctions sequences [ 108 ], and patients developing post-surgical or sudden aortic events are reported [ 109 , 110 , 111 ]. COL3A1 variants were additionally found to be associated with sporadic forms of TAAD in recent WES and case-control studies [ 112 , 113 ]. The type of variant involving the COL3A1 gene was also been suggested to correlate with the phenotype severity of vEDS; specifically, a subgroup of patients in a large European cohort bearing non-glycine missense and/or genetic variations at the C- and N-termini of type III procollagens was found to develop a later-onset and a milder phenotype with higher rates of aortic complications [ 114 ], while mutations at splice-donor sites were associated with higher mortality rates with respect to those involving the splice-acceptor sequences [ 115 ].…”
Section: Mechanisms Of Taa Progression: the Dissection Menacementioning
confidence: 99%